Mouthwash With A Combination Extract Of Butterfly Pea Flower And Mint Leaves As Anti-Inflammatory In Traumatic Ulcer Sufferers At RSGM Unimus - Ayu Puspaning Tyas, Dyah; Megawati, Ani; Kamaruddin, Mudyawati; Sulistyorini, Ratna (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Semarang, 2025)
Traumatic ulcers are mucosal injuries that trigger inflammation, requiring safe and effective alternative therapies. Butterfly Pea flowers and Mint leaves contain bioactive compounds with potential anti inflammatory effects. The purpose of this study was to determine the effectiveness of Telang flower and Mint leaf mouthwash as an anti-inflammatory in patients with traumatic ulcers. The research method used was laboratory experimental with pre-post study design was conducted on 28 respondents using three formulation concentrations (10%, 30% and 50%). The results showed that the mouthwash with Telang flower and Mint leaf extracts had good organoleptic test results, a normal pH test and a good viscosity test. In the Wilcoxon test results, it was found that there were differences before and after the use of Telang flower and Mint leaf extract mouthwash at concentrations of 10%, 30% and 50% with a p-value<α (0.05). This study concludes that the mouthwash combination of Telang flower and Mint leaf extracts at a concentration of 10%, 30%, and 50% effective for anti-inflammatory.